Two‐stage surgery to repair a dissecting abdominal aortic aneurysm in a severely obese patient: Open bifurcated graft replacement after laparoscopic sleeve gastrectomy. Issue 2 (May 2016) - Shioi, Yoshihiro; Sasaki, Akira; Nitta, Hiroyuki; Umemura, Akira; Baba, Shigeaki; Iwaya, Takeshi; Kimura, Yusuke; Otsuka, Koki; Koeda, Keisuke; Mizuno, Masaru; Kumagai, Kazuya; Kamada, Takeshi; et al.
Abstract: With the increasing prevalence of severe obesity worldwide, surgical treatment for severely obese patients is becoming more popular. Bariatric surgery has occasionally been performed as a precursor to major operations for serious diseases to make these difficult surgeries safer for severely obese patients. We present the case of a severely obese patient with a dissected abdominal aortic aneurysm and left iliac artery aneurysm. Initially, we performed bariatric surgery on this patient to reduce perioperative risk and then subsequently performed bifurcated graft replacement. A 54‐year‐old man presented at our hospital for bariatric surgery before open abdominal aortic aneurysm repair. Laparoscopic sleeve gastrectomy was performed; 15 months later, the patient's weight and BMI had decreased from 139.0 kg to 97.6 kg and from 48.7 kg/m 2 to 34.2 kg/m 2, respectively. Bifurcated graft replacement was performed safely without postoperative complications. Bariatric surgery was also effective in controlling the patient's blood pressure during the interval between surgeries.